INVESTMENT ACTIVITY OF COMMERCIAL BANKS IN KAZAKHSTAN: RENDS, PROBLEMS, AND PROSPECTS - SALIKHOVA, Alfia (CENTRAL ASIA AND THE CAUCASUS, 2007)
International intergovernmental organizations and developed countries recognize the Kazakhstan economy as the most dynamically developing in the post-Soviet expanse. Kazakhstan is the first CIS state to be endowed with the status of a market-economy country by the U.S. and European Union. Development of the Kazakhstan economy in recent years has been promoted by the stabilization on the world financial markets and the favorable price situation on the commodity markets, which stimulated and then led to the rapid growth of the global economy. The upswing in the world economy increased the demand for primary products and had a favorable effect on the economy of developing countries. Beginning in 2000, the country’s economic development has been moving forward in leaps and bounds. The average annual rate of Kazakhstan’s GDP increment for 2000-2006 was more than 10%, and the GDP in nominal terms and in the dollar equivalent increased approximately three-fold during this period.1 The high prices for Kazakhstani export goods, primarily for energy resources and metals, was the main factor in economic growth. The annual rise in the price of oil, followed by that of other primary products, was particularly conducive to boosting the domestic economy. At the same time, the export volumes also rose, which in general ensured a significant annual increase in profit for exporters and the inflow of freely convertible currency revenue into the country. The development of the export branches pulled the rest of the economy along with them. Growth of the domestic economy is promoted by the strong tax policy, stable budget balance, rational exchange policy, and increase in real personal incomes.